Task Scheduling and Resource Optimization in Cloud Computing Using Deadline-Aware Particle Swarm Technique - Shruti; Sharma, Meenakshi (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is defined as that type of computing which shows the development of potential, grid and parallel computing. It is the fastest new paradigm for delivery of services via internet. In this, the client can access software resources and valuable information over a network. It is the internet based computing in which resources are accessed via internet. In practice, the cloud computing faces the number of challenges like reliability, portability and shared access etc. Moreover, cloud computing faces the large quantity of cloud users, their tasks and data. Hence, to schedule the tasks efficiently, scheduling is done. In this paper, a Deadline Aware Particle Swarm Optimization (DAPSO) Algorithm is used which provides efficient and better results. Due to its fast convergence property, it is much better than Particle Swarm Optimization (PSO) algorithm. It is used to optimize the task scheduling algorithm which results in better performance and profit.